Chitosan graft copolymer, preparation method thereof and drilling fluid

By introducing specific structural units into chitosan graft copolymers, drilling fluid with good solid wall and filtration loss reduction effects was prepared, and the problems of instability and filtration loss reduction problems in the existing technology were solved, and the problems of walls of the easily collapsed formations were realized. It combines the stability improvement of well walls and environmental protection performance.

CN119431669AActive Publication Date: 2025-02-14CHINA PETROLEUM & CHEMICAL CORP +3

Patent Information

Application Number
CN202310962104.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14
Estimated Expiration
2043-08-01

AI Technical Summary

Technical Problem

When the prior art deals with stratification crack development and crushing zones, the anti-collapse effect of solid walls is limited, and the filtration loss performance is poor. Commonly used wall-restraining agents are prone to failure at high temperatures, which affects the environment.

Method used

A chitosan graft copolymer was developed to prepare a drilling fluid with good solid wall and filter loss reduction effects by introducing structural units A and structural units B into the chitosan structure and controlling the content of each structural unit.

Benefits of technology

It has achieved effective wall solidification and filter loss reduction for stratification crack development and crushing zones such as crushing zones, improved the stability of the well wall, and was not biotoxic and green and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431669A_ABST
    Figure CN119431669A_ABST
Patent Text Reader

Abstract

The invention relates to the field of oilfield chemical drilling fluid treatment agents, and discloses a chitosan grafted copolymer, a preparation method thereof and a drilling fluid, the chitosan grafted copolymer has a structure as shown in formula (I), and the number-average molecular weight is 200000-600000; m is 1200 to 3500, and X and Z are respectively and independently H or-R1COOM1 or a polymeric chain segment; wherein R1 is alkylene of C1-C5, and M1 is H, Na or K; the polymeric chain segment contains a structural unit A and a structural unit B, the structural unit A contains at least two-COOM2, M2 is H, Na or K, and the structural unit B contains a cyclic lactam structure; y is H or a quaternary ammonium salt structure with an ester group. The chitosan grafted copolymer provided by the invention has relatively good wall fixing performance and filtrate loss reduction performance, and ensures well wall stability of easy-to-collapse stratum of shale fracture zone from two aspects of wall fixing and filtrate invasion reduction, # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemical drilling fluid treating agents, and in particular to a chitosan graft copolymer and a preparation method thereof and drilling fluid. Background Art

[0002] In recent years, with the continuous expansion of oil and gas exploration and development, more and more highly active shale, bedding fractures, fracture zones and other easily collapsed formations have been encountered, and the difficulty of wellbore stability has become increasingly greater. Among them, for highly active shale formations, the existing strong inhibitors such as polyether amino alkyl glycoside, polyether amine, and polyamine have been able to solve the problem well; while for formations with bedding fractures, fracture zones and other easily collapsed formations, not only the drilling fluid is required to have strong inhibition performance, but also higher requirements are put forward for chemical wall solidification performance and filtrate invasion reduction performance.

[0003] In recent years, commonly used inhibitors for wall solidification mainly include silicates, silicones, and polymerized aluminum. They use the temperature, pH, mineralization, and other conditions after entering the formation to achieve the effect of depositing and blocking bedding cracks or generating cementing and sealing shells through physical or chemical changes, thereby achieving the purpose of blocking or consolidating the wellbore. However, the actual wall solidification and anti-collapse effect of the above-mentioned inhibitors is limited, the rheology of the drilling fluid is greatly affected, high temperature is easy to fail, and the environment is affected, and the filtration loss reduction effect is poor, resulting in stress changes in the filtrate invading the formation and causing wellbore collapse. In order to better solve the problems of wellbore instability and filtration loss reduction in formations prone to collapse such as bedding fractures and broken zones, the performance of existing commonly used inhibitors for wall solidification needs to be improved. In addition to strengthening the wall solidification inhibition performance, it is also necessary to strengthen and improve the filtration loss reduction performance to meet the technical requirements for wellbore stability in formations prone to collapse such as bedding fractures and broken zones. Therefore, it is necessary to develop an efficient wall solidification and filtration loss reduction agent that has both wall solidification and filtration loss reduction effects to meet the urgent needs of on-site technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem that the prior art lacks both good wall-fixing and fluid loss reduction effects, and to provide a chitosan graft copolymer and a preparation method thereof and a drilling fluid. The chitosan graft copolymer provided by the present invention has good wall-fixing and fluid loss reduction effects, is non-biologically toxic, and is green and environmentally friendly.

[0005] In order to achieve the above object, the first aspect of the present invention provides a chitosan graft copolymer, wherein the chitosan graft copolymer has a structure shown in formula (I) and a number average molecular weight of 200000-600000;

[0006]

[0007] m is 1200-3500, X and Z are independently H or -R1COOM1 or a polymer segment, and the content of the polymer segment is 0.15-20wt% based on the total amount of the chitosan graft copolymer; wherein R1 is a C1-C5 alkylene group, M1 is H, Na or K; the polymer segment contains a structural unit A and a structural unit B, the structural unit A contains at least two -COOM2, M2 is H, Na or K, and the structural unit B contains a cyclic lactam structure; and Y is H or a quaternary ammonium salt structure with an ester group.

[0008] Preferably, the mass ratio of -R1COOM1 to the polymer segment is 1:1-1.5, and the mass ratio of the structural unit A to the structural unit B in the polymer segment is 1:0.5-2.

[0009] Preferably, Y is H or

[0010] wherein R2-R4 are each independently H or C1-C5 alkyl, preferably H; R5 is C1-C5 alkylene; R6-R8 are each independently C1-C5 alkyl; T - F - , Cl - Br - or I - , preferably Cl - .

[0011] Preferably, the structural unit A is a structural unit having a structure represented by formula (1), and the structural unit B is a structural unit having a structure represented by formula (2);

[0012]

[0013] Among them, R9-R 13 Each is independently H or a C1-C5 alkyl group, preferably H; M2 and M3 are each independently H, Na or K.

[0014] A second aspect of the present invention provides a method for preparing a chitosan graft copolymer, the method comprising the following steps:

[0015] (1) subjecting chitosan to a carboxylation reaction with a halogenated carboxylic acid represented by formula (II) to obtain a first intermediate product;

[0016] (2) subjecting the first intermediate product to an addition reaction with a quaternary ammonium salt represented by formula (III) to obtain a second intermediate product;

[0017] (3) in the presence of an initiator, subjecting the second intermediate product to a graft copolymerization reaction with a monomer in water; wherein the monomer comprises: a monomer A' and a monomer B', wherein the monomer A' is a monomer having a structure represented by formula (1'), and the monomer B' is a monomer having a structure represented by formula (2');

[0018]

[0019]

[0020] Among them, R1-R 13 The definitions are the same as those above; T is F, Cl, Br or I, preferably Cl.

[0021] The third aspect of the present invention provides a chitosan graft copolymer prepared by the method described in the second aspect.

[0022] A fourth aspect of the present invention provides a drilling fluid, wherein the drilling fluid comprises the chitosan graft copolymer described in the first aspect or the third aspect as a fluid loss reducer.

[0023] Through the above technical solution, the present invention can achieve the following beneficial effects:

[0024] The chitosan graft copolymer provided by the present invention has good wall consolidation performance and filtration loss reduction performance in drilling fluid, has no biological toxicity, and is green and environmentally friendly. The chitosan graft copolymer provided by the present invention has a good chemical consolidation effect on the well wall, and has a good wall consolidation effect on easily collapsed formations such as bedding fractures and broken zones, while preventing the filtrate from invading the formation to cause stress changes, and has a good filtration loss reduction effect, and can better solve the problem of well wall instability in easily collapsed formations such as bedding fractures and broken zones on site, and meet the technical requirements for well wall stability in easily collapsed formations such as bedding fractures and broken zones. Moreover, in the preparation process of the chitosan graft copolymer provided by the present invention, the reaction conditions are mild, water is used as the solvent, the reaction energy consumption is low, and there is no discharge of wastewater, waste gas, and waste residue. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the infrared spectrum of the sample prepared in Example 1 of the present invention;

[0026] Figure 2 (a)-(d) are photos of the core column without soaking, the core column soaked in clean water, the core column soaked in the sample of Example 1, and the core column soaked in the comparative example sample, respectively. DETAILED DESCRIPTION

[0027] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0028] In the present invention, the C1-C5 alkyl group refers to an alkyl group having 1 to 5 carbon atoms; the C1-C5 alkylene group refers to an alkylene group having 1 to 5 carbon atoms.

[0029] The first aspect of the present invention provides a chitosan graft copolymer, wherein the chitosan graft copolymer has a structure shown in formula (I) and a number average molecular weight of 200,000-600,000;

[0030]

[0031] m is 1200-3500, X and Z are independently H or -R1COOM1 or a polymer segment, and the content of the polymer segment is 0.15-20wt% based on the total amount of the chitosan graft copolymer; wherein R1 is a C1-C5 alkylene group, M1 is H, Na or K; the polymer segment contains a structural unit A and a structural unit B, the structural unit A contains at least two -COOM2, M2 is H, Na or K, and the structural unit B contains a cyclic lactam structure; and Y is H or a quaternary ammonium salt structure with an ester group.

[0032] The inventors of the present invention have found in their research that by simultaneously introducing structural unit A and structural unit B into the chitosan structure and controlling the content of each structural unit within the above range, the obtained chitosan graft copolymer has a good fluid loss reduction effect.

[0033] In the present invention, the C1-C5 alkylene group may be linear, branched, or cyclic, for example, it may be -CH2-, -CH2CH2-, or -CH2CH2CH2-.

[0034] In a preferred embodiment of the present invention, Y is H or

[0035] wherein R2-R4 are each independently H or C1-C5 alkyl, preferably H; R5 is C1-C5 alkylene; R6-R8 are each independently C1-C5 alkyl, preferably methyl; - F - , Cl - Br - or I - , preferably Cl -.

[0036] In the present invention, R6 to R8 may be the same or different, but are preferably the same.

[0037] In the present invention, the C1-C5 alkyl group may be linear, branched, or cyclic, for example, -CH3, -CH2CH3, -CH2CH2CH3, -CH(CH3)2, or -C(CH3)3.

[0038] In a preferred embodiment of the present invention, the mass ratio of -R1COOM1 to the polymeric segment is 1:1-1.5, and the mass ratio of the structural unit A to the structural unit B in the polymeric segment is 1:0.5-2.

[0039] In a preferred embodiment of the present invention, the structural unit A is a structural unit having a structure shown in formula (1):

[0040] Among them, R9-R 10 Each is independently H or a C1-C5 alkyl group, preferably H; M3 and M4 are each independently H, Na or K.

[0041] In a preferred embodiment of the present invention, the structural unit B is a structural unit having a structure shown in formula (2);

[0042]

[0043] Among them, R 11 -R 13 Each is independently H or a C1-C5 alkyl group.

[0044] In the present invention, when R9-R 13 When each is H, structural unit A can be a structural unit provided by maleic anhydride, and structural unit B can be a structural unit provided by N-vinyl caprolactam. That is, in a specific embodiment of the present invention, the polymer segment in the chitosan graft copolymer structure includes structural units provided by maleic anhydride and N-vinyl caprolactam.

[0045] In a preferred embodiment of the present invention, the polymer segment further contains at least one of a structural unit C, a structural unit D, a structural unit E and a structural unit F; wherein the structural unit C is at least one selected from the structural units having a structure represented by formula (3), the structural unit D is a structural unit having a structure represented by formula (4), the structural unit E is a structural unit having a structure represented by formula (5), and the structural unit F is a structural unit having a structure represented by formula (6);

[0046]

[0047] Among them, R 14 -R 16 , R 19 -R 21 , R 23 -R 25 , R 28 -R 30 Each is independently H or a C1-C5 alkyl group, preferably H;

[0048] R 17 is -CO-O;

[0049] R 18 , R 22 , R 26 Each is independently a bond or a C1-C5 alkylene group;

[0050] R 27 is a C1-C5 alkyl group, preferably -CH3, -CH2CH3, -CH(CH3)2, -C(CH3)3;

[0051] M5 and M6 are each independently H, Na or K.

[0052] In the present invention, when R 14 -R 16 H, R respectively 17 -CO-O, R 18 When R is a C4 alkylene group, the structural unit C is a structural unit provided by acryloyloxybutanesulfonic acid. 19 -R 21 H, R respectively 22 When R is a bond, the structural unit D is a structural unit provided by acrylonitrile. 23 -R 25 H, R respectively 26 When R is a bond, the structural unit E is a structural unit provided by vinyltrialkoxysilane. 23 -R 30 Each is H, and the structural unit E is a structural unit provided by sulfonated styrene. That is, in a specific embodiment of the present invention, the polymer segment in the chitosan graft copolymer structure also includes a structural unit provided by at least one of acryloxybutanesulfonic acid, acrylonitrile, sulfonated styrene and vinyltrialkoxysilane.

[0053] In a preferred embodiment of the present invention, the vinyltrialkoxysilane is at least one selected from vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane and vinyltri-tert-butoxysilane.

[0054] In a preferred embodiment of the present invention, the mass ratio of chitosan, structural unit A, structural unit B, structural unit C, structural unit D, structural unit E and structural unit F is 1: (1.6-3): (2-4): (2.5-4): (1-2.5): (3-5.5): (4-5), preferably 1: (2-3): (2.5-4): (3-4): (1-2): (3-5): (4-4.5).

[0055] The inventors of the present invention have found in their research that, by introducing structural unit C on the basis of the polymer chain segment of the chitosan graft copolymer containing unit A and structural unit B, and controlling the content of each structural unit within the above range, the fluid loss reduction effect of the chitosan graft copolymer can be further improved.

[0056] Furthermore, based on the structural unit A, structural unit B and structural unit C contained in the polymer chain segment of the chitosan graft copolymer, the structural unit D is introduced, and the content of each structural unit is controlled within the above range, which can further improve the fluid loss reduction effect of the chitosan graft copolymer.

[0057] Furthermore, based on the fact that the polymer chain segment of the chitosan graft copolymer contains structural unit A, structural unit B, structural unit C and structural unit D, structural unit E is introduced, and the content of each structural unit is controlled within the above range. In addition to having a good filtration loss reduction effect, the chitosan graft copolymer also has good wall solidification performance.

[0058] Furthermore, on the basis of the chitosan graft copolymer containing structural unit A, structural unit B, structural unit C, structural unit D and structural unit E in the polymer chain segment, the structural unit F is introduced, and the content of each structural unit is controlled within the above range, which can further improve the chitosan graft copolymer's fluid loss reduction effect and wall fixing performance.

[0059] The second aspect of the present invention provides a method for preparing a chitosan graft copolymer. According to a preferred embodiment, the method comprises the following steps:

[0060] (1) alkalizing and gelatinizing a chitosan aqueous solution with an alkaline compound and an alcohol compound, and then subjecting the product obtained by the alkalization and gelatinization to a carboxylation reaction with a halogenated carboxylic acid represented by formula (II) to obtain a first intermediate product;

[0061] (2) subjecting the first intermediate product to an addition reaction with a quaternary ammonium salt represented by formula (III) to obtain a second intermediate product;

[0062] (3) in the presence of an initiator, subjecting the second intermediate product to a graft copolymerization reaction with a monomer in water; wherein the monomer comprises: a monomer A' and a monomer B', wherein the monomer A' is a monomer having a structure represented by formula (1'), and the monomer B' is a monomer having a structure represented by formula (2');

[0063]

[0064]

[0065] Among them, R 1 -R 13 The definitions are the same as those above; T is F, Cl, Br or I, preferably Cl.

[0066] In the present invention, an alkaline compound and an alcohol compound are first used to activate a chitosan aqueous solution, and then the activated chitosan is modified by using a halogenated carboxylic acid and a quaternary ammonium salt in sequence, and then the modified chitosan is grafted with a monomer A' and a monomer B' to obtain the chitosan graft copolymer. The chitosan graft copolymer provided by the present invention has good wall-fixing performance and fluid loss reduction performance in drilling fluid, has no biological toxicity, and is green and environmentally friendly. In addition, in the preparation process of the chitosan graft copolymer provided by the present invention, the reaction conditions are mild, water is used as a solvent, the reaction energy consumption is low, and no wastewater, waste gas, and waste residue are discharged.

[0067] In a preferred embodiment of the present invention, in step (1), chitosan is activated by alkalizing and gelatinizing chitosan using alkaline compounds and alcohol compounds, so that chitosan is easy to undergo subsequent reactions.

[0068] In the present invention, in order to promote the full progress of the alkalization gelatinization process, the conditions of the alkalization gelatinization include: a temperature of 55-70°C, preferably 56-67°C, a time of 0.5-2h, and the alkalization gelatinization is carried out under stirring conditions.

[0069] In a preferred embodiment of the present invention, the alkaline compound is selected from sodium hydroxide and / or potassium hydroxide.

[0070] In a preferred embodiment of the present invention, the alcohol compound is selected from at least one of ethanol, glycerol and isopropanol.

[0071] In a preferred embodiment of the present invention, the mass ratio of chitosan, water, alkaline compound and alcohol compound is 1:(10-30):(1-3):(2-5). When the amount of each raw material is within the above range, it can be ensured that chitosan is fully activated.

[0072] In a preferred embodiment of the present invention, in order to promote the full progress of the carboxylation reaction, the conditions of the carboxylation reaction include: temperature of 70-85° C., time of 3-6 h, and pH value of 9-11.

[0073] In the present invention, in order to make the pH value of the solution for the carboxylation reaction meet the above conditions, an alkaline pH regulator commonly used in the art can be used for adjustment. Preferably, the alkaline pH regulator is selected from sodium hydroxide or potassium hydroxide.

[0074] In a preferred embodiment of the present invention, in order to ensure that the activated chitosan is fully modified, the mass ratio of chitosan to halogenated carboxylic acid is 1:(3-5), preferably 1:(4-5).

[0075] In the present invention, there is no particular limitation on the type of the halogenated carboxylic acid, as long as it has the structure shown in formula (II). Preferably, the halogenated carboxylic acid is selected from at least one of chloroacetic acid, 3-chloropropionic acid and 4-chlorobutyric acid.

[0076] In a preferred embodiment of the present invention, in order to allow the first intermediate product to fully react with the quaternary ammonium salt to generate the second intermediate product, the conditions of the addition reaction include: a temperature of 105-130° C. and a time of 2-4 h.

[0077] In a preferred embodiment of the present invention, the mass ratio of chitosan to quaternary ammonium salt is 1:(3-5), preferably 1:(4-5). By adopting this preferred solution, it can be ensured that the first intermediate product is fully modified by the quaternary ammonium salt.

[0078] In the present invention, there is no particular limitation on the type of the quaternary ammonium salt, as long as it has the structure shown in formula (III). Preferably, the quaternary ammonium salt is selected from methacryloyloxyethyl trimethylammonium chloride and methacryloyloxyethyl trimethylammonium bromide.

[0079] In a preferred embodiment of the present invention, the step (3) comprises: mixing the second intermediate product, monomer A' and monomer B' in water to obtain a mixture; adding an initiator to the mixture for graft copolymerization to obtain a reaction product, and then drying, granulating and crushing the reaction product to obtain the chitosan graft copolymer.

[0080] In the present invention, there is no particular limitation on the mixing conditions, as long as the second intermediate product, monomer A' and monomer B' can be fully dissolved. Preferably, the mixing is performed under heating conditions, and the heating temperature is 45-68°C.

[0081] In a preferred embodiment of the present invention, in order to promote the sufficient reaction of the second intermediate product with the monomer, the conditions of the graft copolymerization reaction include: temperature of 75-95°C, preferably 78-94°C, time of 2-8h, pH value of 8-10. Preferably, the graft copolymerization reaction is carried out under the protection of an inert gas, and the inert gas is selected from nitrogen or argon.

[0082] In the present invention, in order to make the pH value of the solution for graft copolymerization reaction meet the above conditions, an alkaline pH regulator commonly used in the art can be used for adjustment. Preferably, the alkaline pH regulator is selected from sodium hydroxide or potassium hydroxide.

[0083] In a preferred embodiment of the present invention, the monomer A' is a monomer having a structure represented by formula (1'). Preferably, the monomer A' is selected from maleic anhydride.

[0084] In a preferred embodiment of the present invention, the monomer B' is a monomer having a structure represented by formula (2'). Preferably, the monomer B' is selected from N-vinyl caprolactam.

[0085] In the present invention, there is no particular limitation on the type and amount of the initiator, and it can be any of the conventional initiators used in the art. Preferably, the initiator is selected from at least one of dibenzoyl peroxide, ammonium persulfate, cerium ammonium nitrate and azobisisobutylamidine hydrochloride.

[0086] In a preferred embodiment of the present invention, the mass ratio of chitosan to initiator is 1:(0.05-0.2). By adopting this preferred embodiment, the chitosan graft copolymer obtained has good fluid loss reduction performance.

[0087] In a preferred embodiment of the present invention, in order to improve the fluid loss reduction performance and wall fixing performance of the prepared chitosan graft copolymer, in step (3), the monomers for graft copolymerization further include at least one of monomer C', monomer D', monomer E' and monomer F'; wherein the monomer C' is at least one selected from monomers having a structure shown in formula (3'), the monomer D' is a monomer having a structure shown in formula (4'), the monomer E' is a monomer having a structure shown in formula (5'), and the monomer F' is a monomer having a structure shown in formula (6');

[0088]

[0089] Among them, R 14 -R 30 The definitions are the same as those described above, and M5 and M6 are H, Na or K.

[0090] In a preferred embodiment of the present invention, the monomer C' is selected from acryloxybutanesulfonic acid; the monomer D' is selected from acrylonitrile; the monomer E' is selected from vinyltrialkoxysilane; and the monomer F' is selected from sulfonated styrene.

[0091] The three alkoxy groups in monomer E' may be the same or different, preferably the same, and all are alkoxy groups with carbon atoms of 1 to 4. In a preferred embodiment of the present invention, the vinyltrialkoxysilane is selected from vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane or vinyltri-tert-butoxysilane.

[0092] In a preferred embodiment of the present invention, the mass ratio of chitosan, monomer A', monomer B', monomer C', monomer D', monomer E' and monomer F' is 1: (1.6-3): (2-4): (2-4): (1-2.5): (3-5.5): (4-5), preferably 1: (2-3): (3-4): (2.5-4) (1-2): (3-5): (4-4.5). By adopting this preferred embodiment, the wall-fixing performance and fluid loss reduction performance of the chitosan graft copolymer prepared can be improved.

[0093] According to a particularly preferred embodiment of the present invention, the preparation method of the chitosan graft copolymer used as the fluid loss reducer comprises the following steps: (1) adding chitosan (polymerization degree m is 1200-3500) to distilled water, stirring evenly, adding alkaline compounds such as sodium hydroxide and alcohol compounds such as ethanol, stirring evenly and then performing alkalinization gelatinization reaction, then adding halogenated carboxylic acid such as chloroacetic acid represented by formula (II), stirring evenly and then adjusting the pH value of the reaction solution to 9-11 for carboxylation reaction for 3-6 hours to obtain an intermediate product A1;

[0094] (2) adding a quaternary ammonium salt represented by formula (III), such as methacryloyloxyethyl trimethylammonium chloride, to the intermediate product A1 for addition reaction to obtain an intermediate product B1;

[0095] (3) adding the monomers required for the reaction into distilled water and stirring evenly to obtain a monomer aqueous solution; adding the monomer aqueous solution into the intermediate product B1 and stirring evenly to adjust the pH value to 8-10; adding an initiator such as dibenzoyl peroxide initiator under nitrogen protection to carry out graft copolymerization; drying, granulating and crushing to obtain a chitosan graft copolymer, which can be directly used as a fluid loss reducer for drilling fluid without further separation and purification.

[0096] The third aspect of the present invention provides a chitosan graft copolymer prepared by the method described in the second aspect. The chitosan graft copolymer provided by the present invention has good wall solidification and fluid loss reduction performance in drilling fluid, and is non-biologically toxic and environmentally friendly.

[0097] A fourth aspect of the present invention provides a drilling fluid, wherein the drilling fluid comprises the chitosan graft copolymer described in the first aspect or the third aspect as a fluid loss reducer.

[0098] In a preferred embodiment of the present invention, based on the total amount of the drilling fluid, the content of the chitosan graft copolymer is 0.15-20wt%, preferably 0.5-10wt%, further 0.5-5wt%, and even more preferably 0.5-3wt%.

[0099] In the present invention, there is no special limitation on other components in the drilling fluid except the chitosan graft copolymer. Those skilled in the art can select drilling fluid components to prepare the drilling fluid according to actual needs, and the present invention does not limit this.

[0100] The present invention will be described in detail below by way of examples. In the following examples and comparative examples, the raw materials involved are all commercially available unless otherwise specified.

[0101] Example 1

[0102] (1) 12 g of chitosan (polymerization degree m is 1500) was added to 200 g of distilled water, and the mixture was stirred evenly. 20 g of sodium hydroxide and 30 g of ethanol were added, and the mixture was stirred evenly. Alkaline gelatinization reaction was carried out at 56° C. for 0.5 h. 42 g of chloroacetic acid was added, and the mixture was stirred evenly. The pH value of the reaction solution was adjusted to 9 with a 20 wt % sodium hydroxide aqueous solution. The reaction was carboxylated at 72° C. for 3 h to obtain an intermediate product A1.

[0103] (2) adding 44 g of methacryloyloxyethyl trimethylammonium chloride to the intermediate product A1, and conducting an addition reaction at 108° C. for 2 h to obtain an intermediate product B1;

[0104] (3) 32 g of acryloxybutanesulfonic acid, 22 g of maleic anhydride, 18 g of acrylonitrile, 24 g of N-vinyl caprolactam, 43 g of vinyl trimethoxysilane, and 48 g of sulfonated styrene are added to 300 g of distilled water and stirred evenly to obtain a monomer aqueous solution; the monomer aqueous solution is added to the intermediate product B1, stirred evenly, heated to 45° C., the pH value is adjusted to 8 with a 20 wt % sodium hydroxide aqueous solution, 0.9 g of dibenzoyl peroxide initiator is added under nitrogen protection, and graft copolymerization is carried out at 78° C. for 2 h. The chitosan graft copolymer is obtained by drying, granulating, and crushing.

[0105] The product prepared in Example 1 of the present invention was subjected to infrared testing, and the infrared spectrum was as follows: Figure 1 Shown: at 1596cm -1 The characteristic absorption peak of chitosan NH is 1216 cm -1 The characteristic absorption peak of C=O bond is 1356cm -1The characteristic absorption peak of the quaternary ammonium group is 2213 cm -1 The characteristic absorption peak of carbon-nitrogen triple bond is 1045cm -1 It is the characteristic absorption peak of sulfonic acid group, 1403cm -1 The characteristic absorption peak of lactam is 1253 cm -1 The characteristic absorption peak of silane is shown in Fig. 2, which indicates that carbonyl, quaternary ammonium, cyano, sulfonic acid, lactam and silane groups are introduced into the molecular structure of chitosan.

[0106] According to the calculation of the feed amount (the same below), based on the chitosan feed amount, in the structure of the product prepared in Example 1 of the present invention, the mass ratio of structural unit A, structural unit B, structural unit C, structural unit D, structural unit E and structural unit F is 22:24:32:18:43:48. The number average molecular weight of the chitosan graft copolymer measured by gel chromatography is 278,000.

[0107] Example 2

[0108] (1) 12 g of chitosan (polymerization degree m is 2000) is added to 240 g of distilled water, stirred evenly, 22 g of potassium hydroxide and 35 g of glycerol are added, stirred evenly, alkalized and gelatinized at 58° C. for 1.0 h, 44 g of 3-chloropropionic acid is added, stirred evenly, the pH value of the reaction solution is adjusted to 10 with a 20% potassium hydroxide aqueous solution, and carboxylation reaction is carried out at 75° C. for 4 h to obtain an intermediate product A2;

[0109] (2) adding 46 g of methacryloyloxyethyl trimethylammonium chloride to the intermediate product A2, and conducting an addition reaction at 115° C. for 3 h to obtain an intermediate product B2;

[0110] (3) 36 g of acryloxybutanesulfonic acid, 24 g of maleic anhydride, 22 g of acrylonitrile, 28 g of N-vinyl caprolactam, 48 g of vinyl triethoxysilane, and 50 g of sulfonated styrene are added to 350 g of distilled water and stirred evenly to obtain a monomer aqueous solution; the monomer aqueous solution is added to the intermediate product B2, stirred evenly, heated to 50° C., the pH value is adjusted to 9 with a 20% potassium hydroxide aqueous solution, 1.1 g of ammonium persulfate initiator is added under helium protection, and graft copolymerization is carried out at 84° C. for 4 hours. The chitosan graft copolymer is obtained by drying, granulating, and crushing.

[0111] Based on the amount of chitosan, the mass ratio of structural unit A, structural unit B, structural unit C, structural unit D, structural unit E and structural unit F in the structure of the product prepared in Example 2 of the present invention is 12:14:18:11:24:25. The number average molecular weight of the chitosan graft copolymer measured by gel chromatography is 371,000.

[0112] Example 3

[0113] (1) 12 g of chitosan (polymerization degree m is 3000) is added to 280 g of distilled water, stirred evenly, 24 g of sodium hydroxide and 45 g of isopropanol are added, stirred evenly, alkalized and gelatinized at 60° C. for 1.5 h, 50 g of 4-chlorobutyric acid is added, stirred evenly, the pH value of the reaction solution is adjusted to 11 with 20% sodium hydroxide aqueous solution, and carboxylation reaction is carried out at 78° C. for 5 h to obtain intermediate product A3;

[0114] (2) adding 50 g of methacryloyloxyethyl trimethylammonium chloride to the intermediate product A3, and conducting an addition reaction at 120° C. for 4 h to obtain an intermediate product B3;

[0115] (3) Add 42 g of acryloxybutanesulfonic acid, 26 g of maleic anhydride, 24 g of acrylonitrile, 30 g of N-vinyl caprolactam, 52 g of vinyl triisopropoxysilane, and 52 g of sulfonated styrene to 400 g of distilled water, stir evenly, and obtain a monomer aqueous solution; add the monomer aqueous solution to the intermediate product B3, stir evenly, heat to 60° C., adjust the pH value to 10 with a 20% sodium hydroxide aqueous solution, add 1.5 g of ammonium cerium nitrate initiator under nitrogen protection, graft copolymerize at 90° C. for 6 h, dry, granulate, and crush to obtain a chitosan graft copolymer.

[0116] Based on the amount of chitosan, in the structure of the product prepared in Example 3 of the present invention, the mass ratio of structural unit A, structural unit B, structural unit C, structural unit D, structural unit E and structural unit F is 13:15:21:12:26:26. The number average molecular weight of the chitosan graft copolymer measured by gel chromatography is 556,000.

[0117] Example 4

[0118] (1) 12 g of chitosan (polymerization degree m is 1800) is added to 300 g of distilled water, stirred evenly, 26 g of sodium hydroxide and 50 g of isopropanol are added, stirred evenly, alkalized and gelatinized at 67° C. for 2 h, 54 g of chloroacetic acid is added, stirred evenly, the pH value of the reaction solution is adjusted to 11 with 20% sodium hydroxide aqueous solution, and carboxylation reaction is carried out at 81° C. for 6 h to obtain intermediate product A4;

[0119] (2) adding 52 g of methacryloyloxyethyl trimethylammonium chloride to the intermediate product A4, and conducting an addition reaction at 130° C. for 4 h to obtain an intermediate product B4;

[0120] (3) Add 48 g of acryloxybutanesulfonic acid, 28 g of maleic anhydride, 28 g of acrylonitrile, 32 g of N-vinyl caprolactam, 55 g of vinyl trimethoxysilane, and 54 g of sulfonated styrene to 450 g of distilled water, stir evenly, and obtain a monomer aqueous solution; add the monomer aqueous solution to the intermediate product B4, stir evenly, heat to 68° C., adjust the pH value to 10 with a 20% sodium hydroxide aqueous solution, add 1.8 g of azobisisobutylamidine hydrochloride initiator under nitrogen protection, graft copolymerize at 94° C. for 8 h, dry, granulate, and crush to obtain a chitosan graft copolymer.

[0121] Based on the amount of chitosan, the mass ratio of structural unit A, structural unit B, structural unit C, structural unit D, structural unit E and structural unit F in the structure of the product prepared in Example 4 of the present invention is 28:32:48:28:55:54. The number average molecular weight of the chitosan graft copolymer measured by gel chromatography is 333,000.

[0122] Example 5-12

[0123] The chitosan graft copolymer was prepared according to the method of Example 4, except that in step (3), the monomer components and amounts used in the preparation of the monomer aqueous solution were as shown in Table 1.

[0124] Table 1

[0125]

[0126] Comparative Example 1

[0127] The chitosan graft copolymer was prepared according to the method of Example 4, except that in step (3), 28 g of maleic anhydride was not added during the preparation of the monomer aqueous solution.

[0128] Comparative Example 2

[0129] The chitosan graft copolymer was prepared according to the method of Example 4, except that in step (3), 32 g of N-vinyl caprolactam was not added during the preparation of the monomer aqueous solution.

[0130] Test Example 1

[0131] The wall-fixing and cementing properties of the samples prepared in Examples 1-12 and Comparative Examples 1-2 of the present invention were tested. The specific operation process was as follows: core columns were soaked in samples with a mass concentration of 3 wt % at 240° C. for 16 h, and the compressive strength of the core columns was tested.

[0132] Figure 2 (a) is a photograph of an un-immersed core column. Figure 2 (b) is a photo of the core column immersed in clean water. Figure 2(c) is a photograph of a core column soaked with 3 wt% of the sample from Example 1. Figure 2 (d) is a photo of a core column soaked with 3 wt% of the sample of comparative example 1. Figure 2 It can be seen that the core column soaked in clean water is severely hydrated and muddy, and the shape of the core column is incomplete; the core column soaked in Example 1 has a complete appearance without cracks, and there is an adsorption film on the surface, showing good wall solidification and filtration loss reduction performance; the core column soaked in Comparative Example 1 has many cracks on the appearance and severe cracking, indicating that the filtrate has serious intrusion. Combined with the compressive strength results in Table 2, it can be seen that the wall solidification effect of Comparative Example 1 is not obvious.

[0133] The compressive strength test method of the soaked core column is as follows: the soaked core column is placed on a compressive strength tester, and the load is increased at a rate of 0.5-0.8 MPa per second until the pressure at which the column is destroyed is the compressive strength. The test results are shown in Table 2.

[0134] Table 2 Test results of the compressive strength of the core column in the embodiments and comparative examples

[0135]

[0136]

[0137] It can be seen from Table 2 that the chitosan graft copolymer prepared in the embodiment of the present invention exhibits outstanding wall-solidifying and bonding properties.

[0138] Test Example 2

[0139] The plugging and filtration reduction performance of the samples prepared in Examples 1-12 and Comparative Examples 1-2 of the present invention was tested. Specifically, the effect of chitosan graft copolymer samples with a mass concentration of 3 wt% on the filtration loss of 4 wt% sodium bentonite-based slurry was tested. The test conditions were: high temperature aging at 240°C for 16 hours.

[0140] The preparation method of 4wt% sodium bentonite-based slurry is as follows: add 2g of anhydrous sodium carbonate and 40g of sodium bentonite for drilling fluid test into 1L of water, stir for 20min, and then cure at room temperature for 24h to prepare the slurry.

[0141] According to the standard of GB / T 16783.1-2014 "Field Test of Drilling Fluids in Petroleum and Natural Gas Industry Part 1: Water-Based Drilling Fluids", the filtration loss before and after adding 3wt% of the embodiment and comparative example samples to 4wt% sodium bentonite-based slurry was tested, and the test results are shown in Table 3.

[0142] Table 3

[0143] Test pulp Filtrate loss FL / mL Sodium bentonite based slurry 53 Sodium bentonite base slurry + Example 1 sample 8.0 Sodium bentonite base slurry + Example 2 sample 6.0 Sodium bentonite base slurry + 3 Example 3 sample 5.0 Sodium bentonite base slurry + 3 Example 4 sample 4.0 Sodium bentonite base slurry + 3 Example 5 sample 18.4 Sodium bentonite base slurry + 3 Example 6 sample 18.2 Sodium bentonite base slurry + 3 Example 7 sample 19.6 Sodium bentonite base slurry + 3 Example 8 sample 18.0 Sodium bentonite base slurry + 3 Example 9 sample 18.6 Sodium bentonite base slurry + Example 10 sample 18.4 Sodium bentonite base slurry + Example 11 sample 19.8 Sodium bentonite base slurry + Example 12 sample 19.3 Sodium bentonite base slurry + comparative example 1 sample 30.2 Sodium bentonite base slurry + comparative example 2 sample 30.8

[0144] It can be seen from Table 3 that the chitosan graft copolymer samples prepared in the examples of the present invention exhibit outstanding plugging and fluid loss reduction performance.

[0145] Test Example 3

[0146] The biotoxicity of the chitosan graft copolymer samples prepared in Examples 1-12 of the present invention and the samples prepared in Comparative Examples 1-2 were tested.

[0147] Biotoxicity EC 50 The test method of the value is as follows: add the samples of the embodiment and comparative example provided by the present invention into a sodium chloride solution with a mass concentration of 3%, and prepare 0 mg.dm -3 、5000mg.dm -3 、10000mg.dm -3 , 25000mg.dm -3 、50000mg.dm -3 、100000mg.dm -3 10 mL of the sample solution to be tested was added to the sample solution to be tested, and then 10 mg of luminescent bacteria T3 powder was added to the sample solution to be tested, and then the biological toxicity EC of the luminescent bacteria after contacting with the sample solution for 15 minutes was measured using a 3 wt% sodium chloride solution as a comparison. 50 Value. 50 When the value is ≥30000 mg / L, it is considered to be non-biologically toxic and is within the permissible discharge standard. The test results are shown in Table 4.

[0148] Table 4

[0149] Test samples <![CDATA[Biotoxicity EC 50 value / ×10 5 mg / L]]> toxicity Example 1 5.43 No biological toxicity Example 2 5.49 No biological toxicity Example 3 5.88 No biological toxicity Example 4 5.74 No biological toxicity Example 5 5.23 No biological toxicity Example 6 5.12 No biological toxicity Example 7 5.25 No biological toxicity Example 8 5.35 No biological toxicity Example 9 5.20 No biological toxicity Example 10 5.04 No biological toxicity Embodiment 11 5.09 No biological toxicity Example 12 5.06 No biological toxicity Comparative Example 1 4.99 No biological toxicity Comparative Example 2 4.78 No biological toxicity

[0150] It can be seen from the experimental results in Table 4 that the EC of the samples of the embodiments of the present invention is 50 Value ≥5.04×10 5 mg / L, far greater than the emission standard of 30000mg / L, non-biological toxicity, green and environmentally friendly.

[0151] It can be seen from the above examples that the chitosan graft copolymer provided by the present invention has good wall consolidation performance and fluid loss reduction performance, and ensures the stability of the well wall in the easily collapsed formation of the shale fracture zone from the two aspects of wall consolidation and reducing filtrate invasion.

[0152] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A chitosan graft copolymer, characterized in that: The chitosan graft copolymer has a structure shown in formula (I) and a number average molecular weight of 200,000-600,000; m is 1200-3500, X and Z are each H or -R1COOM1 or a polymer segment, and the content of the polymer segment is 0.15-20wt% based on the total amount of the chitosan graft copolymer; wherein R1 is a C1-C5 alkylene group, M1 is H, Na or K; the polymer segment contains a structural unit A and a structural unit B, the structural unit A contains at least two -COOM2, M2 is H, Na or K, and the structural unit B contains a cyclic lactam structure; Y is H or a quaternary ammonium salt structure with an ester group.

2. The chitosan graft copolymer according to claim 1, wherein Y is H or wherein R2-R4 are each independently H or C1-C5 alkyl, preferably H; R5 is C1-C5 alkylene; R6-R8 are each independently C1-C5 alkyl; T - F - , Cl - Br - or I - , preferably Cl - .

3. The chitosan graft copolymer according to claim 1 or 2, wherein The mass ratio of -R1COOM1 to the polymer segment is 1:1-1.5, and the mass ratio of the structural unit A to the structural unit B in the polymer segment is 1:0.5-2.

4. The chitosan graft copolymer according to any one of claims 1 to 3, wherein The structural unit A has a structure shown in formula (1), and the structural unit B has a structure shown in formula (2); Among them, R9-R 13 Each is independently H or a C1-C5 alkyl group, preferably H; M3 and M4 are each independently H, Na or K.

5. The chitosan graft copolymer according to any one of claims 1 to 4, wherein The polymer segment further contains at least one of a structural unit C, a structural unit D, a structural unit E and a structural unit F; preferably, the polymer segment further contains a structural unit C, a structural unit D, a structural unit E and a structural unit F; wherein the structural unit C has a structure shown in formula (3), the structural unit D has a structure shown in formula (4), the structural unit E has a structure shown in formula (5), and the structural unit F has a structure shown in formula (6); Among them, R 14 -R 16 , R 19 -R 21 , R 23 -R 25 , R 28 -R 30 Each is independently H or a C1-C5 alkyl group, preferably H; R 17 is -CO-O; R 18 , R 22 , R 26 Each is independently a bond or a C1-C5 alkylene group; R 27 is a C1-C5 alkyl group, preferably -CH3, -CH2CH3, -CH(CH3)2, -C(CH3)3; M5 and M6 are each independently H, Na or K.

6. The chitosan graft copolymer according to claim 5, wherein The mass ratio of the chitosan, structural unit A, structural unit B, structural unit C, structural unit D, structural unit E and structural unit F is 1: (1.6-3): (2-4): (2.5-4): (1-2.5): (3-5.5): (4-5), preferably 1: (2-3): (2.5-4): (3-4): (1-2): (3-5): (4-4.5).

7. A method for preparing a chitosan graft copolymer, characterized in that: The method comprises the following steps: (1) subjecting chitosan to a carboxylation reaction with a halogenated carboxylic acid represented by formula (II) to obtain a first intermediate product; (2) subjecting the first intermediate product to an addition reaction with a quaternary ammonium salt represented by formula (III) to obtain a second intermediate product; (3) in the presence of an initiator, subjecting the second intermediate product to a graft copolymerization reaction with a monomer; wherein the monomer comprises: a monomer A' and a monomer B', wherein the monomer A' has a structure represented by formula (1'), and the monomer B' has a structure represented by formula (2'); Among them, R1-R 13 The definition is the same as that in claim 1 or 2 or 4; T is F, Cl, Br or I, preferably Cl.

8. The method according to claim 7, wherein: The monomer further comprises at least one of monomer C', monomer D', monomer E' and monomer F'; wherein the monomer C' has a structure as shown in formula (3'), the monomer D' has a structure as shown in formula (4'), the monomer E' has a structure as shown in formula (5'), and the monomer F' has a structure as shown in formula (6'); Among them, R 14 -R 30 The definition is the same as that in claim 5, and M5 and M6 are H, Na or K.

9. The method according to claim 8, wherein: The mass ratio of chitosan, monomer C', monomer D', monomer E' and monomer F' is 1:(2-4):(1-2.5):(3-5.5):(4-5), preferably 1:(2.5-4):(1-2):(3-5):(4-4.5).

10. The method according to any one of claims 7 to 9, wherein: The mass ratio of chitosan, halogenated carboxylic acid and quaternary ammonium salt is 1:(3-5):(3-5); Preferably, the mass ratio of chitosan, monomer A', and monomer B' is 1:(1.6-3):(2-4), more preferably 1:(2-3):(3-4); Preferably, the polymerization degree of the chitosan is 1200-3500.

11. The method according to any one of claims 7 to 10, wherein: The halogenated carboxylic acid is selected from at least one of chloroacetic acid, 3-chloropropionic acid and 4-chlorobutyric acid; Preferably, the quaternary ammonium salt is selected from methacryloyloxyethyl trimethylammonium chloride; Preferably, the initiator is selected from at least one of dibenzoyl peroxide, ammonium persulfate, cerium ammonium nitrate and azobisisobutylamidine hydrochloride.

12. The method according to any one of claims 7 to 11, wherein: The conditions of the carboxylation reaction include: temperature of 70-85°C, time of 3-6h, pH of 9-11; Preferably, the conditions of the addition reaction include: temperature of 105-130°C and time of 2-4h; Preferably, the conditions of the graft copolymerization reaction include: temperature of 75-95° C., time of 2-8 h, pH value of 8-10, and the graft copolymerization reaction is carried out under the protection of inert gas.

13. The method according to any one of claims 7 to 12, wherein: The method also includes alkalizing and gelatinizing the chitosan in the presence of an alkaline compound and an alcohol compound before the carboxylation reaction, wherein the conditions of the alkalizing and gelatinizing reaction include: a temperature of 55-70° C. and a time of 0.5-2 hours; Preferably, the alkaline compound is selected from sodium hydroxide and / or potassium hydroxide; Preferably, the alcohol compound is selected from at least one of ethanol, glycerol and isopropanol.

14. A chitosan graft copolymer obtained by the method according to any one of claims 7 to 13.

15. A drilling fluid, characterized in that: The chitosan graft copolymer according to any one of claims 1 to 6 and 14 is included as a fluid loss reducer.

16. The drilling fluid according to claim 15, wherein: Based on the total amount of the drilling fluid, the content of the chitosan graft copolymer is 0.15-20wt%, preferably 0.5-10wt%.

Citation Information

Patent Citations

  • Polysaccharide and / or polypeptide based graft polymers as synthetic tannins

    CN103797038A

  • Self-suspending proppants for hydraulic fracturing

    CN104364343A

  • Use of hydrophilic graft copolymers containing n-vinylamine and / or open-chain n-vinylamide units in comsmetic formulations

    US20030199642A1

Cited By

  • Hydrolyzed polyacrylonitrile salt copolymer and preparation method thereof

    CN120484190A

  • Hydrolyzed polyacrylonitrile salt copolymer and method for preparing the same

    CN120484190B

  • Zwitterionic petroleum drilling aid and preparation method thereof

    CN122609208A